ANALISIS DAMPAK PERUBAHAN IKLIM DAN LUAS LAHAN TERHADAP JUMLAH PRODUKSI PADI DI INDONESIA - Cut Putri Mellitha Sari; Asnawi; Umaruddin Usman; Sahta Valentina Banurea (Jurnal Ekonomi Pertanian Unimal, 2025)
Rice production in Indonesia is increasingly threatened by climate change and the reduction of rice field area, while rice remains the main commodity for national food security. This study aims to analyze the effect of temperature, as an indicator of climate change, and rice field area on rice production in Indonesia. The data used are annual time series for the period 2005–2024, obtained from the Central Bureau of Statistic s (BPS) and the Ministry of Agriculture. The research method employed is multiple linear regression, with classical assumption tests, t-tests, and F-tests. The results show that temperature has a significant negative effect on rice production, while rice field area has a significant positive impact. Simultaneously, both variables are shown to influence rice production in Indonesia significantly. These findings indicate that rising temperatures reduce rice productivity, whereas increased agricultural land availability increases output. The implication is that adaptation policies to climate change and the protection of sustainable agricultural land should be prioritised to ensure national food security.